Pneumonia Induced Childhood Erythema Multiforme Minor: A Case Report - Dahliana, Putri; Djawad, Khairuddin; Tabri, Farida (Open Access Macedonian Journal of Medical Sciences, 2021)
Erythema multiforme (EM) is an acute mucocutaneous syndrome mediated by hypersensitivity reactions. Symptoms are often mild and self-limiting but have a high recurrency rate. The disease is more prevalent in adolescents and adults, with incidence in childhood often precipitated by infection of herpes simplex virus type 1. However, EM induced by infection of Mycoplasma pneumonia is a rare occurrence. This paper reports a case of pneumonia induced EM in a 5-year-old child with a typical clinical feature supported by laboratory and chest X-ray features that were confirmed with histopathology. The patient showed significant clinical improvements after antibiotic therapy.